Adherence to respectful maternity care guidelines during COVID-19 pandemic and associated factors among healthcare providers working at hospitals in northwest Ethiopia: A multicenter, observational study - Azmeraw Ambachew Kebede; Birhan Tsegaw Taye; Kindu Yinges Wondie; Agumas Eskezia Tiguh; Getachew Azeze Eriku; Muhabaw Shumye Mihret (Elsevier, 2021)
Background: Respectful maternity care is one of the facilitators of women's access to maternity healthcare services. However, it has been evidenced that maternal healthcare services are compromised during the pandemic of coronavirus disease 19 (COVID-19). Moreover, there was a dearth of evidence on healthcare provider's adherence to respectful maternity care guidelines through direct observation. Hence, this study intended to assess healthcare provider's adherence to respectful maternity care guidelines during COVID-19 in northwest Ethiopia. Methods: A multicenter observational cross-sectional study was conducted at hospitals in northwest Ethiopia from November 15th/2020 to March 10th/2021. A simple random sampling technique was employed to select 406 healthcare providers. Data were collected through face-to-face interviews and direct observation using a structured questionnaire and standardized checklist respectively. The data were entered into Epi Info 7.1.2 and exported to SPSS version 25 for analysis. A binary logistic regression model was fitted. Both bivariable and multivariable logistic regression analyses were undertaken. The level of significance was claimed based on the adjusted odds ratio (AOR) with a 95% confidence interval (CI) at a p-value of ≤0.05. Results: The proportion of healthcare providers adhering to respectful maternity care guidelines during COVID-19 was 63.8% (95% CI: 59.1, 68.4). Job satisfaction (AOR = 1.82; 95% CI: 1.04, 3.18), professional work experience of 3-5 years (AOR = 2.84; 95% CI: 1.74, 4.6) and ≥6 years (AOR = 2.21; 95% CI: 1.11, 4.38), and having education parallel to work (AOR = 0.33; 95% CI: 0.21, 0.51) have an independent statistical significant association with adherence to respectful maternity care guidelines. Conclusion: In this study, six out of ten healthcare providers had good adherence to respectful maternity care guidelines. Ensuring health worker's job satisfaction and providing education opportunities by the government would improve healthcare provider's adherence to respectful maternity care standards.